Trends and variations in postmastectomy radiation therapy for breast cancer in patients with 1 to 3 positive lymph nodes: A National Cancer Data Base analysis. Issue 3 (7th November 2017) - Ohri, Nisha; Sittig, Mark P.; Tsai, Chiaojung Jillian; Hwang, Eun‐Sil Shelley; Mittendorf, Elizabeth Ann; Shi, Weiji; Zhang, Zhigang; Ho, Alice Y.
Abstract : BACKGROUND: High‐level evidence is lacking to guide treatment decisions about postmastectomy radiation therapy (PMRT) in patients who have breast cancer with 1 to 3 positive lymph nodes who receive contemporary systemic therapies, leading to potential variations in PMRT delivery. The objective of this study was to examine nationwide trends in PMRT use in this group. METHODS: The National Cancer Data Base (NCDB) was used to identify 93, 372 women who had T1‐T2N1 breast cancer diagnosed between 2003 and 2012. Patients who received neoadjuvant chemotherapy or radiation therapy (RT) and those who had bilateral breast cancers were excluded. Time trends were evaluated using the Cochrane‐Armitage test and correlated the receipt of PMRT with various patient demographic, facility, clinicopathologic, and treatment variables using multivariable logistic regression. A second analysis was performed for patients who were diagnosed during 2010 and included radiation oncologist density as an additional covariate. P values < .0001 were considered statistically significant. RESULTS: Overall, 22.5% of the study population received PMRT, representing an increase from 19.1% in 2003 to 30.3% in 2012. Factors associated with greater PMRT use included younger age, lower Charlson‐Deyo comorbidity scores, shorter distance to the treating facility, treatment at a comprehensive cancer program, facility location in the New England Census division, and higher density of radiation oncologists. Increased PMRT use was associated with later year of diagnosis, receipt of chemotherapy, receipt of hormone therapy, higher grade disease, larger tumor size, greater numbers of positive lymph nodes, positive margins, and absence of immediate breast reconstruction (all P  < .0001). CONCLUSIONS: The receipt of PMRT by patients with breast cancer who have 1 to 3 positive lymph nodes has increased over time, with wide variability in practice patterns in the United States. Cancer 2018;124:482‐90. © 2017 American Cancer Society . Abstract : Treatment trends for postmastectomy radiation therapy between 2003 and 2012 are evaluated from the National Cancer Data Base among women with T1‐T2 breast tumors and from 1 to 3 positive lymph nodes. Increasing rates of postmastectomy radiation therapy are observed, with variability based on clinicopathologic features, age, and regional density of radiation oncologists.